Simultaneous Determination of Five Active Ingredients in Yixintong Tablet by HPLC - Cheng, Weiming; Gao, Jie; Yue, Chao; Zhang, Wenting (Asian Journal of Chemistry, 2014)
To establish an HPLC method for the simultaneous determination of five active ingredients (glucosyl-vitexin, rhamnosyl-vitexin, vitexin, rutin and hyperin). HPLC conditions included Welch material XB-C18 column (4.6 mm × 250 mm, 5 μm) and the mobile phase was a mixture of tetrahydrofuran (A)-acetonitrile (B)-methanol (C)-0.05 % phosphoric acid (D) at a flow rate of 1 mL/min for gradient elution. The column temperature was 30 °C. Five active ingredients had good linear relationships: glucosyl-vitexin in the range of 0.0369-1.85 μg (R2 = 0.9998), rhamnosyl-vitexin in the range of 0.109-5.47 μg (R2 = 0.9995), vitexin in the range of 0.00600-0.300 μg (R2 = 0.9999), rutin in the range of 0.00510-0.255 μg (R2 = 0.9997) and hyperin in the range of 0.00510-0.255 μg (R2 = 0.9997). Their average recoveries were 97.55 % (RSD = 1.9 %), 98.27 % (RSD = 2.1 %), 98.22 % (RSD = 2.4 %), 97.55 % (RSD = 2.1 %) and 98.13 % (RSD = 2.6 %), respectively. This method was steady with high precision and good repeatability. It could be used for the determination of the five active ingredients and quality control of Yixintong tablet.